A protocol for developing, disseminating, and implementing a core outcome set (COS) for childbirth pelvic floor trauma research - Stergios K. Doumouchtsis; Maria Patricia Rada; Vasilios Pergialiotis; Gabriele Falconi; Jorge Milhem Haddad; Cornelia Betschart (BMC, 2020)
Abstract Background More than 85% of women sustain different degrees of trauma during vaginal birth. Randomized controlled trials on childbirth pelvic floor trauma have reported a wide range of outcomes and used different outcome measures. This variation restricts effective data synthesis, impairing the ability of research to inform clinical practice. The development and use of a core outcome set (COS) for childbirth pelvic floor trauma aims to ensure consistent use of outcome measures and reporting of outcomes. Methods An international steering group, within CHORUS, an International Collaboration for Harmonising Outcomes, Research and Standards in Urogynaecology and Women's Health, including academic community members, researchers, healthcare professionals, policy makers and women with childbirth pelvic floor trauma will lead the development of this COS. Relevant outcome parameters will be identified through comprehensive literature reviews. The selected outcomes will be entered into an international, multi-perspective online Delphi survey. Subsequently and based on the results of the Delphi surveys consensus will be sought on 'core' outcomes. Discussion Dissemination and implementation of the resulting COS within an international context will be supported and promoted. Embedding the COS for childbirth pelvic floor trauma within future clinical trials, systematic reviews, and clinical practice guidelines is expected to enrich opportunities for comparison of future clinical trials and allow better synthesis of outcomes, and will enhance mother and child care. The infrastructure created by developing a COS for childbirth pelvic floor trauma could be leveraged in other settings, for example, advancing research priorities and clinical practice guideline development.